STRATEGI BERSAING PRODUK KERIPIK TEMPE BU NOER KOTA MALANG DENGAN MENITIKBERATKAN PADA KEGIATAN RANTAI NILAI - , Nadya Paramita Sari ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This paper planned to examine how the competitive strategy adopted by chips tempe Bu Noer Malang that developing its business with the concept of value chain approach. The product is an excellent product from Malang city, the benefits of this product was already known by the public. But the disadvantage is the number of competitors who are also in business. Based on the research findings, it should be more emphasis on the management of competitive strategy in increasing sales. Sample selected using purposive sampling method that is based on certain considerations in accordance with the purpose of research. There are three stages that do the identifying value chain activities, identify cost drivers in each activity value and develop competitive advantage by reducing costs or add value. Value added which can be given to consumers not only on the issue of assurance of raw materials but also on aspects of their own products which could be raised a degree, not only food product but the packaging can be useful information for tourists. While the cost reduction can be done by doing promo on free media like social networking, or government-owned tourism bulletins for the development of the management UMKM.